The Impact of Global Liquidity on Financial Landscapes and Risks in the ASEAN-5 Countries - Sun, Tao (IMF Working Papers; Working Paper ;, 2015)
This paper analyzes the transmission of global liquidity to the ASEAN-5 countries (ASEAN-5), including the impact on financial landscapes and risks to financial stability. It finds that global liquidity transmission and changing financial landscapes have contributed to increases in risks to financial stability in ASEAN-5. Therefore, policymakers in ASEAN-5 should prepare for possible liquidity tightening, strengthen regulation of nonbanks, and establish a comprehensive financial stability framework. A number of couontries are well-advanced in this process.